Marriage, adaptation and happiness: Are there long-lasting gains to marriage? - Salmai Qari (Verein für Socialpolitik, 2010)
This paper uses 23 waves of German panel data and investigates if individuals who decide to marry become permanently happier. Following the same persons over several years we show that they do, thereby challenging a number of recent longitudinal studies in psychology and economics which suggest that individuals fully adapt to the positive impact of marriage. We then convert the estimates into Euro values. It is well known that most newlyweds experience a 'honeymoon period' shortly after marriage. We calculate the monetary equivalent of being married for five years to avoid overestimation due to this honeymoon effect. These long-run monetary benefits are quite large, e.g. for males on average 85,000 Euros a year. This supports the findings by Blanchflower and Oswald (2004, Journal of Public Economics) which are based on cross-sectional data.
Keywords: J12; I31; J10; 330